2016
DOI: 10.3389/fpsyt.2016.00176
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Review of microRNA Expression Patterns in Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by a wide spectrum of deficits in social interaction, communication, and behavior. There is a significant genetic component to ASD, yet no single gene variant accounts for >1% of incidence. Posttranscriptional mechanisms such as microRNAs (miRNAs) regulate gene expression without altering the genetic code. They are abundant in the developing brain and are dysregulated in children with ASD. Patterns of miRNA expression are altered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 70 publications
1
99
1
Order By: Relevance
“…We show here that the levels of eight oral taxa may distinguish children with ASD from TD peers, while a panel of five taxa classifies ASD and DD subjects, both with nearly 80% accuracy. Previously, we have demonstrated that microRNA levels in saliva may differentiate children with ASD from healthy controls [Hicks & Middleton, ]. It is intriguing to consider that some perturbations in salivary microRNA may be driven by host interactions with the microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…We show here that the levels of eight oral taxa may distinguish children with ASD from TD peers, while a panel of five taxa classifies ASD and DD subjects, both with nearly 80% accuracy. Previously, we have demonstrated that microRNA levels in saliva may differentiate children with ASD from healthy controls [Hicks & Middleton, ]. It is intriguing to consider that some perturbations in salivary microRNA may be driven by host interactions with the microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…We identified target genes of dysregulated miRNAs through in silico analysis and negative regulatory interactions between differentially expressed miRNAs and putative targets in ASD. Although gene and miRNA expression profiles have been previously studied, they have typically involved non‐cerebral tissue, such as blood or lymphoblast cell lines, or postmortem brains in human cases 10. Considering that ASD is a developmental disorder of the brain, brain tissue from adult cases as well as non‐cerebral tissue may not be optimal targets for investigating disease processes during the early developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…Altered miRNA expression has been associated with neurological disorders, including Alzheimer's disease,6 schizophrenia,7 and ASD 8, 9. Therefore, miRNAs may act as epigenetic factors in complex ASD etiologies, however, there have been substantial differences reported in miRNA expression profiles among different studies 10. Furthermore, studies of human ASD cases cannot investigate miRNA changes during earlier developmental stages.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reviewed the findings of 12 publications which compared miRNA from ASD patients to miRNA profiles from healthy controls in different tissues and biofluids including the brain, peripheral blood, saliva, olfactory precursor cells and cultured lymphoblast (Hicks and Middleton, 2016). It's worth noting that some of the mentioned salivary miRNA where also found dysregulated in brain tissue (miR‐335‐3p and miR‐27a‐3p, the latter also in blood) (Hicks and Middleton, 2016) which underlines their relevance as potential ASD biomarkers from saliva.…”
Section: Resultsmentioning
confidence: 99%